Implementasi Pemberian Royalti bagi Pemegang Hak Cipta Terkait Pendistribusian Musik Melalui Platform SoundOn pada Aplikasi TikTok - Salsabila, Nisrina Zulfa; Roisah, Kholis (UNES Law Review, 2024)
Distribution of music through digital platforms, such as SoundOn on TikTok, has become a dominant phenomenon in the modern music industry. However, the implementation of royalty distribution to copyright holders has become a significant concern in this context. This research employs a normative research approach to analyze the legal foundations, policies, and practices related to royalty distribution to copyright holders in the distribution of music through the SoundOn platform on TikTok. Evaluation of royalty implementation is conducted by considering transparency, oversight, reporting, and fairness in royalty distribution. Recommendations are provided for improvements, including enhancing transparency, developing algorithms, and consulting with copyright holders. Thus, this study offers valuable insights to improve the practices of fair and sustainable royalty distribution in the digital music industry.